Joseph Conrad’s Heart of Darkness: An Exploration of Human Interiority - Dahal, Tara Kumar (International Journal of Humanities, Education, and Social Sciences, 2025)
This paper explores the psychological and moral descent depicted in Joseph Conrad’s Heart of Darkness, arguing that the narrative blurs the boundaries between suppressed inner instincts and the fragile veneer of civilisation. The physical journey into the African interior is interpreted as a metaphorical expedition into the raw core of human nature, where societal norms disintegrate and primal instincts surface. The analysis employs an integrated theoretical framework combining Freudian psychoanalysis—particularly the dynamics of the id, ego, and superego—with existentialist thought, which emphasizes the individual’s search for meaning in an inherently absurd and chaotic world. Through this lens, the study investigates the psychological turmoil and existential crisis experienced by both Marlow and Kurtz, shaped by isolation and the dissolution of moral order. Conrad’s strategic use of literary devices, especially symbolism and spatial imagery—such as the contrast between light and darkness and the portrayal of the Congo—serves to externalize the characters’ internal conflicts and moral corruption. The study concludes that the central horror of Heart of Darkness is not the physical wilderness, but the psychological collapse that ensues when individuals confront the unfiltered depths of their own consciousness, stripped of societal restraints.